Dynamic loading of concentric circular tubes - Hao, L.K.; Ghani, A.R.A.; Edi, P.; Yusuf, K. (2009)
Non-linear finite element code ABAQUS/Explicit was employed to evaluate the energy absorption characteristics of concentric circular tubes subjected to impact in the axial direction. Thin-walled circular tube plays a vital role as energy absorber due to its high energy absorption capacity. However, the main drawback of existing tube type energy absorber is the high initial peak force. This paper evaluates the capability of concentric circular tubes in reducing the peak force that will be exerted to the protected structures and occupants during impact. Clearance of the structure was varied and different materials such as aluminum alloy, high strength steel and stainless steel were applied. This study found that aluminum alloy has great potential to be utilized as energy absorbing system due to its high specific energy absorption capacity and long stroke. Increasing the clearance between the inner and outer circular tubes resulted in a reduction of peak force and a significant increase of specific energy absorption (SEA). This paper revealed that concentric circular tubes could be utilized as a safer design of energy absorber as it exhibited a lower peak force during impact which is a desirable feature when designing for occupant safety.